2009
DOI: 10.1623/hysj.54.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methods for extracting low-resolution river networks from high-resolution digital data

Abstract: A range of methods for deriving lower-resolution river networks from higher-resolution Digital Terrain Model (DTM) data are assessed at various spatial scales. Derived flow networks are compared to fine-scale hydrologically corrected rivers using a range of performance criteria. These include a measure of spatial distance between fine-scale and derived rivers, and criteria which assess errors in derived catchment area. The Network Tracing Method (NTM), a vector-based network scheme, and the COTAT+ method, a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…In topography it is applied to. Indeed, Davies and Bell (2009) found that it performed 20 reasonably accurately across the whole of mainland Britain. Generally the percentage 21 error in catchment area arising from the delineation of a catchment boundary using 22 1km-resolution flow-directions is less than 5%, although a few catchments have larger 23…”
Section: Flow 13 14mentioning
confidence: 98%
“…In topography it is applied to. Indeed, Davies and Bell (2009) found that it performed 20 reasonably accurately across the whole of mainland Britain. Generally the percentage 21 error in catchment area arising from the delineation of a catchment boundary using 22 1km-resolution flow-directions is less than 5%, although a few catchments have larger 23…”
Section: Flow 13 14mentioning
confidence: 98%
“…This has been defined for a regular 1.5 km resolution grid across the UKC2 domain using the GMTED2010 digital terrain model and expert human intervention to ensure that the flows are routed correctly (e.g. Davies and Bell, 2009). For simplicity in initial testing, the river routing was considered on the same grid as the land surface model (i.e.…”
Section: Ukl2 River Routingmentioning
confidence: 99%
“…Net outflow estimates (mm) for each grid-square in each region are converted to monthly-mean river flows (m 3 s −1 ) through lateral transfer of upstream flows from each catchment to the catchment outlet for every river grid-cell, using the 1 km flow directions identified for the kinematic wave routing implemented in the G2G Model (Davies and Bell, 2008;. WBM flows for every 1 km river location are scaled with respect to historical mean WBM flow and these standardized flows are averaged to provide a mean value for each of the 17 geographic regions (Fig.…”
Section: Water-balance Model For Flowsmentioning
confidence: 99%